KAJIAN NILAI-NILAI ISLAM TEMBANG DHANDHANG GULA DALAM SERAT WULANG REH KARYA SRI SUSUHUNAN PAKU BUWANA IV - Imam Mahfud (MUADDIB Jurnal Kependidikan dan Keislaman, 2013)
Dhandang Gula is one of Javanese Song (tembang) of Wulang Reh created by Sri Susuhunan Paku Buwana IV from Surakarta Sultanate. This song includes the islamic values which are needed to be examined and appointed, so the reader, who are moslem mostly, will know and appreciate it. This great work was created 200 years ago by Surakarta Sultan, which is now still used by javanese craftman, especially among the singers (pesinden) or waranggana in uyon-uyon, during the wayang show, as well as any other events. Through this study, the writer found the islamic values including good message or teaching which occured in javanese society, among moslems, or even universally. Those messages were exactly right if it were used as an instruments for educating, teaching, training, guiding, or even worshiping. Thus, it is certainly good if this song mastered by all parents, or whoever wants to deliver a good message.Dhandang Gula is one of Javanese Song (tembang) ofWulang Reh created by Sri Susuhunan Paku Buwana IV from SurakartaSultanate. This song includes the islamic values which are needed to beexamined and appointed, so the reader, who are moslem mostly, willknow and appreciate it. This great work was created 200 years ago bySurakarta Sultan, which is now still used by javanese craftman, especiallyamong the singers (pesinden) or waranggana in uyon-uyon, during thewayang show, as well as any other events. Through this study, the writerfound the islamic values including good message or teaching whichoccured in javanese society, among moslems, or even universally. Thosemessages were exactly right if it were used as an instruments foreducating, teaching, training, guiding, or even worshiping. Thus, it iscertainly good if this song mastered by all parents, or whoever wants todeliver a good message.